Treatment of Nitrogen Heterocyclic Compounds (NHCs) in Coking Wastewater by White-Rot Fungi - Chaofan Huang; Dajun Ren; Chen Kang; Zhiqun Deng; Huiwen Guo; Shuqin Zhang; Xiaoqing Zhang (Tecnología y ciencias del agua, 2019)
In the present study the white-rot fungi BP was selected to study the degradation of nitrogen heterocyclic compounds in real and simulated coking wastewater. The study incorporated analysis of the degradation process, mechanism of action of white-rot fungi on nitrogen heterocyclic compounds, changes of enzyme activity and white-rot fungi biomass growth rate in coking wastewater (simulated and actual). The results showed that addition of ammonia nitrogen and phenol in simulated wastewater had insignificant effects on the degradation of indole. Moreover, the promoting effect of phenol on quinoline degradation was greater than the inhibition effects of ammonia nitrogen. Degradation rates of quinoline, indole and pyridine are consistent with the zero-order kinetics equation. It was also found that the addition of Mg (II) and Mn (II) promotes the degradation of quinoline by white-rot fungi in the actual wastewater, while degradation of pyridine was inhibited by three ions, out of which the inhibition of Cu (II) was the most obvious. Cu (II) was also found to have positive effects on the levels of activity of laccase enzyme secreted by the white-rot fungi as opposed to other metal ions tested. However, it was found to have inhibitory effects on the development of white-rot fungi, while Mg (II) and Mn (II) were found to promote the development of the white-rot fungi. The activity of the enzyme and the growth rate of biomass of white-rot fungi first reached the maximum levels followed by a significant decline.